3D-Pharmacophore and Molecular Docking Studies for AcrAB-TolC Efflux Pump Potential Inhibitors from DrugBank and Traditional Chinese Medical Database - Phan, Thien-Vy; Nguyen, Cao-Hoang-Hao; Nguyen, Vu-Thuy-Vy (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Due to the widespread resistance to several antibiotics, the AcrAB-TolC tripartite efflux pump is the primary multi-drug efflux system of Escherichia coli. One of the most promising treatments since the discovery of efflux pump inhibitors is the combination of them with antibiotics. AIM: Based on the efflux pump inhibitor database and the structure of AcrB, the research was created the virtual screening models with prediction capabilities for the efflux pump inhibitory effects of candidates from the DrugBank and Traditional Chinese Medical databank. Methods: The pharmacophore models were developed by MOE 2015.10 software using a database of 119 efflux pump inhibitors discovered in 12 research publications and belonged to different structural classes. The binding site was found on the AcrB protein (PDB: 4DX7) by LeadIT 2.0.2 software that corresponds to the hydrophobic trap in the proximal pocket. Results: The potential inhibitors which satisfied the pharmacophore model and had docking scores under -20 kJ.mol-1 have been established. In which, TCM_20290, DB00303, DB04642, DB08116, TCM_29530, and 2,5-dimethyl-3-O-D-glucopyranosyl-naphthol have the best docking scores of -32.76, -26.59, -26.14, -25.62, -24.88, and -22.82 kJ.mol-1, respectively. Conclusions: After the screening, the result was obtained six compounds may be potential efflux pump inhibitors that can be used for additional studies. In the future, further in vitro and in vivo research should be required to confirm the effects of these compounds. The ongoing battle against antibiotic resistance shows promise with the finding on initiators that can obstruct AcrAB–TolC multidrug efflux pumps. Keywords: AcrAB-TolC, inhibitors, Escherichia coli, pharmacophore, molecular docking.